ACCULTURATION STUDY OF RELIGION -CULTURE PERSPECTIVE Q.S. AL-A'RAF [7]: 199 IN THE SUMENEP MADURA PALACE - Aan Najib (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2020)
The acculturation of religion and culture from the perspective of Q.S. Al-A’raf [7]: 199, which begins to be forgotten these days, is an important element in the history of the Sumenep palace in Madura. The methods used in this research are qualitative, descriptive, literature, and field research methods. This research is intended to address 1) What are the cultural differences before and after the entry of Islam in the Sumenep Palace, 2) What are the changing elements in the lives of the Madurese people affected by the acculturation in the Sumenep Palace, 3) explore and find ethical solutions in responding to community attitudes toward Sumenep Palace by analyzing the interpretation of QS. Al-A’raf [7]: 199. The scientific contribution of this research is in the form of encourage- ment to the community so that they have noble values, hard-work spirit, moderate and open mind, fighting spirit, bravery, and patience in facing challenges like those experienced by the palace of Sumenep.